Until the storm passes : politicians, democracy, and the demise of Brazil's military dictatorship - Pitts, Montie Bryan (University of California Press, 2023)
Until the Storm Passes reveals how Brazil's 1964-1985 military dictatorship contributed to its own demise by alienating the civilian political elites who initially helped bring it to power. Based on exhaustive research conducted in nearly twenty archives in five countries, as well as on oral histories with surviving politicians from the period, this book tells the surprising story of how the alternatingly self-interested and heroic resistance of the political class contributed decisively to Brazil's democratization. As they gradually turned against military rule, politicians began to embrace a political role for the masses that most of them would never have accepted in 1964, thus setting the stage for the breathtaking expansion of democracy that Brazil enjoyed over the next three decades.